2021
DOI: 10.3390/ijms22136784
|View full text |Cite
|
Sign up to set email alerts
|

Sp1-Induced FNBP1 Drives Rigorous 3D Cell Motility in EMT-Type Gastric Cancer Cells

Abstract: Cancer is heterogeneous among patients, requiring a thorough understanding of molecular subtypes and the establishment of therapeutic strategies based on its behavior. Gastric cancer (GC) is adenocarcinoma with marked heterogeneity leading to different prognoses. As an effort, we previously identified a stem-like subtype, which is prone to metastasis, with the worst prognosis. Here, we propose FNBP1 as a key to high-level cell motility, present only in aggressive GC cells. FNBP1 is also up-regulated in both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Several researches showed that FNBP1 could affect tumor migration and invasion through affecting the formation of filopodia in bladder cancer [ 64 ] and breast cancer cells [ 65 ]. In addition, a recent study found the loss of FNBP1 could result in the loss of invasive ability in gastric cancer [ 66 ]. Remarkably, a pan-cancer analysis based on bioinformatics found that except the metastatic cancer, low expression of FNBP1 was associated with worse prognosis in breast cancer and lung adenocarcinoma, while high expression of FNBP1 was related to the poor prognosis in stomach adenocarcinoma [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several researches showed that FNBP1 could affect tumor migration and invasion through affecting the formation of filopodia in bladder cancer [ 64 ] and breast cancer cells [ 65 ]. In addition, a recent study found the loss of FNBP1 could result in the loss of invasive ability in gastric cancer [ 66 ]. Remarkably, a pan-cancer analysis based on bioinformatics found that except the metastatic cancer, low expression of FNBP1 was associated with worse prognosis in breast cancer and lung adenocarcinoma, while high expression of FNBP1 was related to the poor prognosis in stomach adenocarcinoma [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 motif-driven FNBP1 expression is a key molecule process in explaining the invasiveness of EMT-type GC cells. Pharmacological inhibition and knockdown of Sp1 down-regulate FNBP1 promoter activity and transcription level, respectively [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in tumor research, independent research on FNBP1 is extraordinarily limited. Only few studies have focused on migration and invasion, such as the three-dimensional movement of gastric cancer cells [ 16 ], suppression of FNBP1 affected the formation of filopodia in bladder cancer [ 19 ] and breast cancer cells [ 37 ]. Therefore, in this study, we used multiple databases for joint analysis to study the role of FNBP1 in a variety of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…FNBP1 had been well documented to be extensively involved in cell motility and endocytosis [16][17][18]. However, emerging evidence indicates a novel role of FNBP1 in malignant tumor invasion and metastasis [19][20][21][22][23][24][25]. Here, FNBP1 was confirmed to play a crucial role in maintaining constitutive FAK/PI3K/AKT/mTOR survival signaling…”
Section: Introductionmentioning
confidence: 87%